2021
DOI: 10.1145/3474664
|View full text |Cite
|
Sign up to set email alerts
|

"My Soul Got a Little Bit Cleaner"

Abstract: Videogames receive increasing acclaim as a medium capable of artistic expression, emotional resonance, and even transformative potential. Yet while discussions concerning the status of games as art have a long history in games research, little is known about the player experience (PX) of games as art, their emotional characteristics, and what impact they may have on players. Drawing from Empirical Aesthetics, we surveyed 174 people about whether they had an art experience with videogames and what emotions they… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Empirical studies showed that video games can generate diverse meaningful experiences such as complex emotional and reflective experiences through relating in-game experiences and out-of-game experiences (Bopp et al, 2016 ; Mekler et al, 2018 ). Also, video games can provide a distant space where players can actively explore their emotions, reflect on their past and present life experiences that resonate with their in-game experiences, and find new meaning and values (Bopp et al, 2021 ; Spors and Kaufman, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies showed that video games can generate diverse meaningful experiences such as complex emotional and reflective experiences through relating in-game experiences and out-of-game experiences (Bopp et al, 2016 ; Mekler et al, 2018 ). Also, video games can provide a distant space where players can actively explore their emotions, reflect on their past and present life experiences that resonate with their in-game experiences, and find new meaning and values (Bopp et al, 2021 ; Spors and Kaufman, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The potential of using meaningful gaming experiences to facilitate bereaved players' meaning-making of loss has received little research attention. Empirical studies suggest that playing video games provided a lifeline for bereaved players overwhelmed by grief (Iacovides and Mekler, 2019 ; Bopp et al, 2021 ), and designing games has been explored as a medium for bereaved individuals to construct their own self-narrative on loss and share their grief experience (Harrer, 2018 ). However, only a few studies have explored how grieving players made new meanings of their loss through playing video games.…”
Section: Introductionmentioning
confidence: 99%